46.6k views
2 votes
Last one plz help guys

Last one plz help guys-example-1
User Androvich
by
4.5k points

1 Answer

2 votes

Answer:

4.1

Explanation:

You can use the Pythagorean Theorem to solve this:


a^(2) + b^(2) = c^(2)

Plug in the numbers into the formula:


4^(2) + 1^(2) = c^(2)

16 + 1 =
c^(2)

17 =
c^(2)

Square both sides:


√(17) = √(c^2)

4.12 = c

4.1 = c

User Alexi Coard
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.